Assessing the Impact of Mutual Funds in Ghana. A Case Study of Databank - Borklo, G.A. (University of Ghana, 2019)
In the last few decades, mutual funds have developed due to the global integration of financial markets. The aim of this study is assessing the role of mutual funds towards increasing the financial gains of investors, using Databank Mutual fund as a case study. The study adopted descriptive research. The simple random sampling method is used to sample the 100 respondents from the Accra and Tema branches of Databank. The study found out that a greater majority of the respondents invest less than 25% of their total income. Concerning how Mutual fund has improved the financial gains of investors, majority of the respondents have benefited from the mutual fund. The study revealed that the impact of mutual on these investors are enormous because investors are motivated by the high return expected from the investment. Similarly, another impact is that mutual fund provides the benefit of risk diversification with a minimum allocation of funds. The study also found out that, respondents benefit from investments with low risk and yet high return. Also, return potential of mutual fund, Professional Management of mutual fund, Regulation of mutual fund and transparency of mutual fund are advantages to investors. The study revealed that people invest in Mutual funds scheme because Mutual funds diversify the risk of the investor by investing in a basket of assets; mutual fund is very simple to invest and monitor fund performance on a regular basis; and Mutual Funds provide the benefit of cheap access to expensive stocks. Based on the findings, the study proffers the following recommendations. That, investment education must be a part of the educational curricular, thus from the basic level to the higher education level. In order to inculcate the habit of investment and better equip individuals on risks associated with the types of investment schemes. In addition, investment companies must increase the interest rate on investment in order to shore up more investors for their schemes. Such innovations would also motivate investors to invest in long-term products rather than the short-term investment as revealed from the study.
MSc.
Keywords: Mutual Funds; Databank